Profiling Microglia From Alzheimer’s Disease Donors and Non-demented Elderly in Acute Human Postmortem Cortical Tissue - Alsema, Astrid M.; Jiang, Qiong; Kracht, Laura; Gerrits, Emma; Dubbelaar, Marissa L.; Miedema, Anneke; Brouwer, Nieske; Hol, Elly M.; Middeldorp, Jinte; van Dijk, Roland; Woodbury, Maya; Wachter, Astrid; et al. (Frontiers in Molecular Neuroscience, 2020)
Microglia are the tissue-resident macrophages of the central nervous system (CNS). Recent studies based on bulk and single-cell RNA sequencing in mice indicate high relevance of microglia with respect to risk genes and neuro-inflammation in Alzheimer’s disease (AD). Here, we investigated microglia transcriptomes at bulk and single-cell levels in non-demented elderly and AD donors using acute human postmortem cortical brain samples. We identified seven human microglial subpopulations with heterogeneity in gene expression. Notably, gene expression profiles and subcluster composition of microglia did not differ between AD donors and non-demented elderly in bulk RNA sequencing nor in single-cell sequencing.